2013
DOI: 10.1186/2192-1709-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Early life on land and the first terrestrial ecosystems

Abstract: Terrestrial ecosystems have been largely regarded as plant-dominated land surfaces, with the earliest records appearing in the early Phanerozoic (<550 Ma). Yet the presence of biological components in pre-Phanerozoic rocks, in habitats as different as soils, peats, ponds, lakes, streams, and dune fields, implies a much earlier type of terrestrial ecosystems. Microbes were abundant by~3,500 Ma ago and surely adapted to live in subaerial conditions in coastal and inland environments, as they do today. This impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 271 publications
(285 reference statements)
2
42
0
Order By: Relevance
“…The Dresser Formation terrestrial hot spring facies include geyserite, siliceous sinter terracettes and the mineralized remnants of hot spring pools. These findings extend the geological record of inhabited terrestrial hot springs by ∼3 billion years, the occurrence of an exposed land surface by up to ∼130 million years3637 and evidence of life on land by ∼580 million years21.…”
Section: Discussionsupporting
confidence: 78%
“…The Dresser Formation terrestrial hot spring facies include geyserite, siliceous sinter terracettes and the mineralized remnants of hot spring pools. These findings extend the geological record of inhabited terrestrial hot springs by ∼3 billion years, the occurrence of an exposed land surface by up to ∼130 million years3637 and evidence of life on land by ∼580 million years21.…”
Section: Discussionsupporting
confidence: 78%
“…If the latter is true, and multiple sources of organic carbon contributed to the sedimentary organic matter preserved in the deposit, as was recently shown to be the case for the Ediacaran Shuram Formation in Oman 60 , then the model presented here could conceivably explain covarying trends in paired d 13 C carb and d 13 C org records from the ancient geological record. Although higher level terrestrial plants were not present until the late Palaeozoic, the presence of terrestrial life in earlier time periods, including photosynthetic cyanobacteria, fungi and algae [61][62][63][64][65][66] , supports the possibility that ancient sedimentary organic carbon could have been composed of mixtures of marine and terrestrial organic carbon, in a situation analogous to the model of subaerial exposure proposed for the Neogene. In fact, the range in d 13 C org values of Precambrian sedimentary organic matter is the largest for any time period in Earth history 67 .…”
Section: Article Nature Communications | Doi: 101038/ncomms5672mentioning
confidence: 87%
“…The appearance of cyanobacterial akinetes (for N 2 fixation) in the Paleoproterozoic [184] attests to this early adaptation. The limiting nutrients such as P, can be supplied for organisms on land by dust deposition [185,186], which may be an alternative process for replenishment of nutrient loss by runoff and leaching in such environments [168,187]; S can also be acquired from minerals, aerosols, and as gaseous sources, likely present in the early atmosphere [188]. Thus, the nutritional requirements for oxygenic, photoautotrophic, primary producers seem not to have been a limiting factor for the colonization of the land.…”
Section: Microbial Biodiversity In Terrestrial Ecosystemmentioning
confidence: 99%
“…A conceptualization of the functioning of the ancient terrestrial biosphere necessarily requires a general understanding of modern, analog microbial communities to evaluate their living requirements, diversity, physiology, and environmental impact, and to characterize any potential biosignature that could be used to recognize them in the rocks [168,169]. Modern terrestrial microbial communities are found worldwide and in a great variety of local conditions, in surface (solid rock, regolith) and subsurface (caves, groundwater, deep ground) environments.…”
Section: Microbial Biodiversity In Terrestrial Ecosystemmentioning
confidence: 99%